Risky behavior in virtual reality: The roles of personality, environment, and physiology - Dejan Pajić; Selka Sadiković; Milan Oljača; Željko Popović; Lazar Milić; Goran Stojanović; Snežana Smederevac (PLoS ONE, 2025)
Virtual reality (VR) provides a unique opportunity to simulate various environments, enabling the observation of human behavior in a manner that closely resembles real-world scenarios. This study aimed to explore the effects of anticipating reward or punishment, personality traits, and physiological arousal on risky decision-making within a VR context. A custom VR game was developed to simulate real-life experiences. The sample comprised 52 students (63.46% female) from the University of Novi Sad, Serbia. The study assessed four parameters within the VR environment: elapsed game time, number of steps taken, average score, and decision-making time. Three physiological signals, heart rate, skin conductance, and respiratory rate, were recorded. Results indicated that personality traits, specifically Fight (β = -0.33, p = 0.024) and Freeze (β = 0.431, p = 0.009), were significantly related to behavior in the VR environment (R = 0.572, R2_adj = 0.227, RMSE = 23.12, F(6, 40) = 3.25, p = 0.011). However, these effects were not significant after negative feedback. Emotional arousal, measured by respiratory rate amplitude (β = 0.276, p = 0.045), showed a more pronounced role after feedback (β = 0.337, p = 0.028). These findings indicate that personality traits primarily influence behavior in a VR environment prior to the actual threat, whereas environmental characteristics become more important afterwards. The results offer valuable insights for experimental and personality psychologists by revealing how risk-taking is influenced by situational, emotional, and personality factors. Additionally, they provide guidance for VR designers in creating more ecologically valid environments, highlighting VR’s potential as a tool for psychological research, while also underscoring the critical importance of selecting objective VR measures to accurately capture the complexities of human behavior in immersive environments.